Mediating the Bullying-to-Delinquency Transition With Peer Delinquency and Cognitive Insensitivity - Walters, Glenn D. (Crime & delinquency, 2023)
This study sought to determine whether peer delinquency, cognitive insensitivity, and/or their interaction mediated the transition from bullying perpetration to delinquency. Data from 845 early adolescent youth (406 boys, 439 girls) organized into three waves were subjected to path analysis, with peer delinquency and cognitive insensitivity as parallel mediators. Results revealed that cognitive insensitivity successfully mediated the relationship between Wave 1 bullying perpetration and Wave 3 participant delinquency, whereas peer delinquency and the peer???insensitivity interaction did not. It would seem that involvement in bullying behavior may lead to a rise in antisocial thinking of the neutralization/moral disengagement type and that this thinking, referred to in this study as cognitive insensitivity, may then stimulate future involvement in delinquent behavior.